Conflict or Fair Deal Between the Generations? Alternative economics for pensions (Szociológiai Szemle, 2023)
For thousands of years, our ancestors operated a pension system that modern economists have declared obsolete, and which a new system has been introduced to replace. However, this new system is beginning to go bankrupt, while the maintaining of the old by the young is increasingly becoming a battle between generations. In other words, the modern pension system – it would seem – has not solved, but exacerbated the pension problem. But the old principle can still be applied, since the upcoming generation does not maintain future pensioners for nothing. Future transfers to the latter by the young have been preceded by transfers from that older generation towards the young. This means that the elderly are justified in demanding a pension from the young, but only those to whom the young owe a debt, and only to the extent of that debt. Having recognised this, we can lay the foundations for a new pension system based on the equitable settling of accounts between generations, which in principle will be similar to the old system, but which provides solutions that are more characteristic of the modern system.